Development of Student Worksheets based on Problem-Solving of Temperature and Heat to Improve the Students Problem-Solving Ability - Ningsih, Puji Wahyu; Putri, Desy Hanisa; Purwanto, Andik (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to describe the feasibility of Student Worksheets based on problem-solving of temperature and heat, describe increasing students' problem-solving ability, and describe students' responses to the Student Worksheets. The method used is Research and Development (R&D) with ADDIE model. Data collection techniques used in this study include interviews, questionnaires, observations, and documentation. The instruments used in this study include observation sheets, interview sheets, needs analysis questionnaire sheets, design validation questionnaire sheets, expert validation sheets, response questionnaire sheets, pretest sheets, and posttest sheets. Pretest sheets and posttest sheets are arranged based on indicators of problem-solving ability. The development process went through validity tests by three experts, and field trials by 36 students. The results showed that the developed Student Worksheets had a percentage of 92% with a very decent category. The average pre-test score and post-test score with N-gain analysis results of 0.79 showed an increase with the high category, while the students' responses showed a percentage of 93% with the very good category. Based on the results of the study, it can be concluded that student worksheets based on problem-solving on temperature and heat are very feasible to be used to improve students' problem-solving abilities in physics learning.